2012
DOI: 10.1128/mmbr.05013-11
|View full text |Cite
|
Sign up to set email alerts
|

The AlternativeTranslational Profile That Underlies the Immune-Evasive State of Persistence in Chlamydiaceae Exploits Differential Tryptophan Contents of the Protein Repertoire

Abstract: SUMMARY One form of immune evasion is a developmental state called “persistence” whereby chlamydial pathogens respond to the host-mediated withdrawal of l -tryptophan (Trp). A sophisticated survival mode of reversible quiescence is implemented. A mechanism has evolved which suppresses gene products necessary for rapid pathogen proliferation but allows expression of gene products that underlie the morphological and developmental characteristics of persistence. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 144 publications
1
41
0
Order By: Relevance
“…C. trachomatis has a degraded cytotoxin, mostly nonfunctional, although differences in functionality at the serovar level have been reported (66). C. muridarum has three paralogous cytotoxin copies (67) and produces functional cytotoxins. Since C. muridarum and C. trachomatis show a difference in their responses to IFN-␥ (32), a cytokine that plays an important role in the early clearance of Chlamydia from the genital tract (68), both species will probably also differ in their responses to other cytokines.…”
Section: Mouse Modelsmentioning
confidence: 99%
“…C. trachomatis has a degraded cytotoxin, mostly nonfunctional, although differences in functionality at the serovar level have been reported (66). C. muridarum has three paralogous cytotoxin copies (67) and produces functional cytotoxins. Since C. muridarum and C. trachomatis show a difference in their responses to IFN-␥ (32), a cytokine that plays an important role in the early clearance of Chlamydia from the genital tract (68), both species will probably also differ in their responses to other cytokines.…”
Section: Mouse Modelsmentioning
confidence: 99%
“…While this provocative hypothesis seems to fit the C. trachomatis data best, it may also be partly supported by the limited C. pneumoniae data that are available. Lo et al (121) reported that MurA is a low-tryptophan-containing enzyme, making it more suited to expression during persistence. Indeed, when Timms et al (123) evaluated murA transcription in the IFN-␥ model of C. pneumoniae, they found that it was upregulated 2-fold under these conditions.…”
Section: Subtle Variations In the Tryptophan Content Of Key Chlamydiamentioning
confidence: 99%
“…Several reviews have emerged recently (121,122) suggesting that the chlamydial genus as a whole may have evolved a mechanism that mutes or downregulates selected gene products via the tryptophan levels in these key proteins. Those proteins that are required during the acute or active growth phase (i.e., normal development of Chlamydia) have higher tryptophan content, since tryptophan availability is less of an issue in this stage of growth.…”
Section: Subtle Variations In the Tryptophan Content Of Key Chlamydiamentioning
confidence: 99%
“…Indeed, RalR strongly activates the transcription of two genes encoding the surface-associated proteins, RalG and Aap (Fig. 5), which contain significantly more tryptophan, 2.4 to 2.6% versus 1.5%, which is the average of the complete E. coli proteome (63). Tryptophan residues are known to help translocation of surface proteins through cell membranes and serve as anchors on the periplasmic side of the membrane (64).…”
Section: Discussionmentioning
confidence: 99%
“…In E. coli, the transcription of the trpEDCBA, mtr, and tnaAB operons is tightly controlled by endogenous levels of tryptophan via TrpR-mediated repression and/or a transcriptional termination mechanism known as attenuation (61,62). Low levels of tryptophan cause an increased expression of trpEDCBA and mtr and reduced expression of tnaAB and vice versa (61)(62)(63). Further analysis using EMSA and promoter-lacZ fusions indicated that RalR neither binds to the regulatory regions of these operons nor directly regulates their expression (data not shown).…”
Section: Discussionmentioning
confidence: 99%